2017
DOI: 10.1111/jgs.15143
|View full text |Cite
|
Sign up to set email alerts
|

Medicaid Cost Savings of a Preventive Home Visit Program for Disabled Older Adults

Abstract: CAPABLE for Frail dually eligible older adults NCT01743495 https://clinicaltrials.gov/ct2/show/NCT01743495.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 24 publications
(23 reference statements)
0
37
0
Order By: Relevance
“…Community programs focusing on function and environment for older people with complex needs have demonstrated improved function, reduced depression and improved motivation to participate in activity (Szanton et al, 2011(Szanton et al, , 2018. Although the low income population studied by Szanton et al (2011) is not directly comparable to an Australian population, findings show early intervention focusing on physical training can improve function, reduce frailty and falls risk, and reduce difficulties with completing ADL tasks.…”
Section: Discussionmentioning
confidence: 99%
“…Community programs focusing on function and environment for older people with complex needs have demonstrated improved function, reduced depression and improved motivation to participate in activity (Szanton et al, 2011(Szanton et al, , 2018. Although the low income population studied by Szanton et al (2011) is not directly comparable to an Australian population, findings show early intervention focusing on physical training can improve function, reduce frailty and falls risk, and reduce difficulties with completing ADL tasks.…”
Section: Discussionmentioning
confidence: 99%
“…Expanding upon ABLE, CAPABLE is a 16-week structured program delivered by OTs who conduct six home visits and provide assistive devices, RNs who conduct four home visits, and a handyman who provides home alterations (ie, installs devices, makes environmental modifications, and performs home repair). [15][16][17][18][19] Similar to ABLE, the CAPABLE interdisciplinary team provided consultation with older adults to help them identify daily activity goals (eg, taking a shower and walking to the bathroom), evaluated barriers to achieving those goals, and attained outcomes collaboratively. 11,18 The OT assists older adults to perform ADLs, instrumental ADLs (IADLs), and discretionary activities that are challenging at home, such as functional mobility, meal preparation, bathing, and dressing.…”
Section: Model Descriptionmentioning
confidence: 99%
“…Nurse practitioners are featured as team leaders in the Geriatric Resources for Assessment and Care of Elders team care model, an early and successful care model implemented and evaluated extensively in lower income older adults in an urban setting very similar to the CAPABLE study sample . In CAPABLE, registered nurses were used as team members; although they have a more limited scope of practice than nurse practitioners, their focus in CAPABLE is on assessment of older adults’ health problems, goal setting, and communication with office‐based primary care providers . Handyman services are a creative addition to an in‐home care team focused on optimizing function and adds a novel dimension to the definition of the direct care workforce that must grow to meet ever‐increasing demands of an aging society …”
Section: Organizational Considerationsmentioning
confidence: 99%
“…In this issue of the Journal of the American Geriatrics Society , Szanton and colleagues reported that an in‐home, multidisciplinary team intervention targeting risk factors for functional decline called the Community Aging in Place, Advancing Better Living for Elders (CAPABLE), was associated with significantly lower Medicaid expenditures . The focus on Medicaid costs was highly appropriate because this study enrolled only older adults who were dually eligible for Medicare and Medicaid.…”
mentioning
confidence: 95%